Comidas del Zopilote - Dominique Raby (Les Cahiers ALHIM)
In this article, ritual food is analyzed in the context of an annual offering to the vulture, during the “rain petition” ceremony in the Alto Balsas Nahua region, México. Using the “multispecies ethnography” perspective, the author underlines how the relations between human beings and the vulture are connected to food and empathy, and how the bird, as cleaner of the world, is involved in the complex network of relations framed by the basic Nahua concepts of working, feeding and loving. The human-vulture relationship culminates in the annual offering, which concentrates in an impressive ritual those concepts and the paper of the bird in the agricultural cycle from which Nahua people were traditionally dependent.